Targeting the environmental assessment of veterinary drugs with the multi-species-soil system (MS·3) agricultural soil microcosms: the ivermectin case study - Carbonell-Martin, G.; Pro-Gonzalez, J.; Aragonese-Grunert, P.; Babin-Vich, M. M.; Fernandez-Torija, C.; Tarazona-Lafarga, J.V. (Spanish Journal of Agricultural Research, 2011)
The environmental risk assessment of the veterinary pharmaceutical ivermectin is receiving significant attention. This paper assesses the capacity of the MS·3 soil microcosm as a tool for targeting the environmental impact assessment of veterinary drugs, using ivermectin as model. Two screening MS·3 were performed using different European soils; one with a soil collected in an agricultural station near to Madrid, Spain and a second with a soil collected in a farm area close to York, UK. Soils were fortified with ivermectin at the following ranges: 0.01-10 mg kg–1 and 0.1-100 mg kg–1 in the Madrid and York studies, respectively. The effects on earthworms, plants and soil microorganisms were assessed in the Madrid soil. Toxicity tests on aquatic organisms (algae, cladocerans and in vitro fish cell line RTLW1) were also conducted with the leachates. No effects were observed in earthworms and plants at any tested concentration; reduction in the respiration rate (< 5%) of soil microorganisms was detected. Earthworm/soil bioconcentration factors decreased with the increase in soil concentrations and were higher for the York soil. Effects on daphnids were observed in tested leachates; based on measured levels of ivermectin in the leachates an EC50 of about 0.5 μgL–1 can be estimated. Comparisons based on toxicity data and equilibrium partitioning confirmed that the main risk is expected to be related to the high sensitivity of cladocerans. The results confirm that MS·3 systems are cost-effective tools for assessing the impact of veterinary pharmaceuticals when applied to agricultural land, as previously demonstrated for antimicrobials.